De novo STAT3 Mutation in a Patient with Fatal, Treatment-Refractory Sino-orbital Aspergillosis. (4th October 2017) - Natarajan, Mukil; Hsu, Amy; Weinreich, Michael; Sugui, Janyce; Zangeneh, Tirdad; Carr, Tara; Oler, Andrew; Similuk, Morgan; Kwon-Chung, Kyung; Milner, Joshua; Lionakis, Michail S
Abstract: Background: Signal transducer and activator of transcription 3 ( STAT3 ) loss-of-function mutations in humans result in Job's syndrome, characterized by elevated IgE, bacterial infections, chronic mucocutaneous candidiasis, pulmonary aspergillosis due to structural lung disease, and connective tissue abnormalities. Methods: Whole exome sequencing (WES) was performed on a putatively immunocompetent patient with sino-orbital aspergillosis and his parents. Evaluation of STAT3 phosphorylation (pSTAT3) was performed by flow cytometry on peripheral blood mononuclear cells after IL-6 stimulation. Results: A 37-year-old-male with a history of eosinophilic esophagitis developed a locally invasive sino-orbital infection with progressive cavernous sinus involvement associated with facial numbness, diplopia, and visual loss. Biopsy showed chronic inflammation and invasive fungal hyphae. Cultures grew an isolate of Aspergillus fumisynnematus that was identified by morphology and the sequences of β-tubulin and Mcm7. MICs (in µg/ml) for the isolate were: micafungin <=0.015, amphotericin 2, posaconazole 0.25, terbinafine 0.06, and voriconazole 0.25. The patient underwent multiple surgical debridements and was treated over time with various antifungals (amphotericin B, micafungin, terbinafine, voriconazole, posaconazole), adjunct cytokines (IFN-γ, GM-CSF), and hyperbaric oxygen. However, the infection progressed into the right middle cranial fossa and meninges and the patient died 1 year after symptoms began. WES revealed a de novo splice-site mutation in STAT3 (c.1140-3C>G). cDNA sequencing showed nonsense mediated decay of the affected allele. No mutations in CARD9 or NADPH oxidase subunits were found; a DHR test was normal. The patient had normal blood myeloid cell subsets. Serum IgE level was elevated at 833 IU/ml. After stimulation with IL-6, the patient's memory CD4+ T cells and CD11c+ myeloid cells had reduced pSTAT3 levels compared with control cells. Cellular analysis of SOCS3, a STAT3-dependent downstream target, is underway to evaluate for functional STAT3 haploinsufficiency. Conclusion: A novel de novo STAT3 splice site mutation results in impaired pSTAT3, and is associated with elevated IgE, eosinophilic esophagitis, and sino-orbital aspergillosis without other common features of Job's syndrome Disclosures: All authors: No reported disclosures.